2017
DOI: 10.1111/exd.13279
|View full text |Cite
|
Sign up to set email alerts
|

Basophils and mast cells are crucial for reactions due to epicutaneous sensitization to ovalbumin

Abstract: The prevalence of food allergies worldwide has increased recently. Epicutaneous sensitization to antigen could be a method to study food allergy. To clarify the mechanisms of food allergy, we established a mouse model of epicutaneous sensitization using ovalbumin (OVA). BALB/c mice were sensitized by three-time application of OVA to tape-stripped skin (1-week sensitization at 2-week intervals) and oral challenge of OVA undertaken. Rectal temperature was monitored. Blood and tissue (skin and jejunum) of challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…Two independent groups [22, 28] reported that the number of mast cells in the small intestine increased after oral antigen challenge in tape-stripping epicutaneously sensitized mice. By contrast, another group [30] reported an increased number of basophils, but not mast cells, in the jejunum after oral OVA challenge in OVA-epicutaneously sensitized mice. Such discrepancy in the behavior of intestinal immune cells might be related to the difference in experimental designs among studies, such as the frequency of sensitizations and the timing of histological observation.…”
Section: Discussion/conclusionmentioning
confidence: 90%
See 3 more Smart Citations
“…Two independent groups [22, 28] reported that the number of mast cells in the small intestine increased after oral antigen challenge in tape-stripping epicutaneously sensitized mice. By contrast, another group [30] reported an increased number of basophils, but not mast cells, in the jejunum after oral OVA challenge in OVA-epicutaneously sensitized mice. Such discrepancy in the behavior of intestinal immune cells might be related to the difference in experimental designs among studies, such as the frequency of sensitizations and the timing of histological observation.…”
Section: Discussion/conclusionmentioning
confidence: 90%
“…Several studies have demonstrated that the accumulation of immune cells in intestine was observed in epicutaneously sensitized mouse models [22, 28-30]. To determine whether immune cells accumulation could be observed in our model, histological analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to their tissue distribution and enzymatic composition of their granules, it is possible to distinguish at least two subpopulations of mast cells: mucosal mast cells, which contain trypsin, and connective tissue mast cells, which contain chymotrypsin. A high-affinity receptor for IgE is expressed by basophils and mast cells, which is strongly bound to their surfaces, leading to degranulation and the release of various substances, including serotonin, histamine, platelet-activating factor, and leukotrienes (Table 1) (133,134).…”
Section: Basophils and Mast Cellsmentioning
confidence: 99%